Willingness to pay for eliminating the risk of being infected by blood-borne diseases in regular replacement treatment for patients with haemophilia - Sara Olofsson; Katarina Steen Carlsson; Erik Berntorp; Emmelie Persson; Flemming Axelsen; Ulf Persson (University of Oslo, 2016)
Hemophilia is a set of lifelong bleeding disorders linked to the X chromosome. Standard treatment for patients with severe hemophilia is intensive replacement therapy with intravenous injection of coagulation factor concentrates to prevent spontaneous recurrent joint bleed. In the 1980s, many hemophilia patients were infected with HIV and/or hepatitis C transmitted by plasma derived coagulation factor concentrates. In the future, new pathogens could appear and a risk remains that the current manufacturing methods will not be able to eliminate those.  The aim of the study is to estimate the value of eliminating the risk of being infected by blood-borne diseases in the treatment of hemophilia which could provide decision-makers with information on how much resource to spend on this purpose to be in line with societal preferences. Individual preferences for safety were elicited from a sample of 821 individuals from the Swedish general population using a web-based questionnaire. The preferences were estimated using the "chained approach" which combines the contingent valuation (CV) and standard gamble (SG) methods. The respondents were asked (1) to state their willingness-to-pay to avoid a temporary, non-fatal injury presented in a health state derived from the EQ-5D instrument, and (2) to choose between living with this injury with certainty or receive a treatment that could restore the respondent to full health immediately, but which entails a risk of being infected by a fatal, blood-borne disease. A value of a statistical life (VSL) in the context of blood-borne diseases of SEK47 million was calculated by "chaining" the answers to the CV question and SG question, and from the VSL we derived a value of a QALY in the context of blood-borne diseases of SEK2.8 million. Using the current mean annual dose of factor concentrate of 268,000 international units (IU) per patient in Sweden, the value of eliminating the risk of being infected by blood-borne diseases would be SEK1.80 per IU corresponding to a price premium of around 45 %. Published: Online April 2016. In print August 2016.